PENGARUH KINERJA KEUANGAN TERHADAP REAKSI PASAR PADA PERUSAHAAN MULTI MEDIA - Ariani, Hilda Mala; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to test the influence of return on assets (ROA), return on equity (ROE), earning per share (EPS), and debt to equity ratio (DER) to the market reaction on the multimedia companies which are listed in Indonesia Stock Exchange in 2010-2013 periods. The research sample has been selected by using non probability sampling. The analysis technique has been done by using multiple regressions analysis. Based on the result of multiple regressions analysis of the significance level is 5% therefore the research shows that: (1) return on assets, it has an influence to the market reaction with the significance level is 0.026. It can be accepted because the value of t-count is 2.320 which show positive direction, (2) return on equity, it has an influence to the market reaction with its significance level is 0.009. It can be accepted because the value of t-count is 2.777 which show a positive direction, (3) earning per share, it has influence to the market reaction with its significance level of 0.021. It can be accepted because the value of t-count is 2.423 which show positive directions, and (4) debt to equity ratio; it has an influence to the market reaction with its significance level of 0.026. It can be accepted because the value of t-count is 2.318 which show positive direction. Therefore, return on assets (ROA), return on equity (ROE), earning per share (EPS), and debt to equity ratio (DER) have positive influence to the market reaction.Keywords: Return on Assets (ROA), Return on Equity (ROE), Earning per Share (EPS), Debt to Equity Ratio (DER), Market Reaction